Meta-analysis of Laying Hen Trials Using Diets With or Without Allzyme® SSF Enzyme Complex - Hooge, D.M.; Pierce, J.L.; McBride, K.W.; Rigolin, P.J. (International Journal of Poultry Science, 2010)
A statistical meta-analysis was conducted using results from 16 laying hen trials (1995-2008; plus some undated reports) from several countries to demonstrate effects of a dietary enzyme complex (+SSF; Allzyme® SSF, Alltech, Inc., Nicholasville, Kentucky USA) versus no supplement (nCON, negative control) on 6 performance parameters. The paired t-test (Statistix 8, Analytical Software, Tallahassee, Florida USA) was used in the statistical analysis. A total of 26 comparisons from 16 trials were possible for hen-day egg production, egg weight and daily egg mass production and 24 comparisons from 14 trials were possible for daily feed intake, feed/dozen eggs and kg feed/kg eggs. Overall averages for the parameters were calculated and levels of significance (p-values) were given. The inclusion rates for the enzyme product in the diets was listed. Hen-day egg production was numerically (p = 0.136) improved by 1.09% actual (+1.29% relative) for +SSF compared to nCON diets. Egg weight was significantly (p = 0.006) greater for eggs from hens fed +SSF rather than nCON diets (+0.89 g or +1.49%). Daily egg mass produced was significantly greater (p = 0.014) for +SSF than for nCON fed hens (+1.74 g/hen/day or +3.47%). Feed intake was numerically (p = 0.281) lowered by 0.50 g/hen daily (-0.44%) by using +SSF diets compared to nCON diets. Feed/dozen eggs was significantly (p = 0.028) reduced by 0.027 kg/dozen (1.65%) and kg feed/kg eggs was significantly (p = 0.004) reduced by 0.069 (3.04%) for +SSF diets compared to nCON diets. Enzyme supplementation (Allzyme® SSF) at 150 g/tonne of feed is recommended to improve the egg weight, daily egg mass and feed conversion ratios of laying hens.